Open Schools for Open Societies Special Issue - Fermeli, Georgia (Open Schools Journal for Open Science, 2021)
This issue presents 6 articles written by students from across Greece in collaboration with their teachers/mentors in the framework of OSOS and R4C European projects that presented in the international online congress «Open and Distance Education: New challenges and Perspectives» that took place in Athens, 6-8/11/2020.